Comparison of balance control in female athletes in different sports - Shahheidari, S.; Norasteh, A. A.; Mohebbi, H. (Medicina dello Sport, 2012)
Aim. Previous work has suggested that the level of activity and the type of sport both may have a major impact on postural control. But few authors have undertaken studies to compare the effects of different type of sport on static and dynamic balance. The aim of this study was to compare static and dynamic balance among athletes competing or training in swimming, soccer, basketball and gymnastic.